Standard Patient Evaluation of Eye Dryness (SPEED) and Ocular Surface Disease Index (OSDI) Scores in Dry Eye Disease Patients - Haider, Golam; Kadir, Syeed Mehbub Ul; Shultana, Razia; Chowdhury, Nuzhat Tabassum; Imran, Al (Community Based Medical Journal, 2025)
Dry eye disease (DED) is a common multifactorial ocular surface state that affects quality of life. A cross-sectional study was conducted in Bangladesh Eye Hospital and Institute, Dhaka, Bangladesh, between January and December of 2024, to assess the impact of age and gender on the severity of dry eye disease (DED) as determined by Standard Patient Evaluation of Eye Dryness (SPEED) and Ocular Surface Disease Index (OSDI) scores. A total of 200 patients, who exhibited symptoms of dry eye disease (DED), were included in this study. They were asked to complete the SPEED and OSDI questionnaires. SPEED and OSDI scores were analyzed by gender and age groups (25–35, 36–45, 46–55, and 56–65 years). The patients aged between 25 and 65 years (mean age was 46.52 years). Among them, 83 were male and 117 were female (male-female ratio was 1:1.41). Regarding SPEED score, 25–35 years age group having the highest mean score (2.84), which indicates more severe symptoms. Regarding OSDI scores, patients in 36-45 years and 25-35 years age groups exhibited the highest mean scores (1.85±0.71 and 1.80±0.76 respectively). In contrast, older patients (56–65 years age group) demonstrated lower score (1.60±0.79), which indicates variation in symptom severity as individual is ageing. In SPEED scores, female patients had slightly higher mean compared to males (2.66±0.65 vs. 2.79±0.54), although the difference was less pronounced. In OSDI scores, male patients were marginally higher compared to females (1.81±0.79 vs. 1.69±0.70); however, the difference was not significant. Gender and age have a big impact on DED symptoms. Our results signify the need for specialized management plans for DED considering demographic variables. CBMJ 2025 July: vol. 14 no. 02 P:154-157